Assessing Seed Transmission Rate and Efficacy of Seed Applied Plant Protection for Bacterial Leaf Streak in Hard Red Spring Wheat - Gabriel Dusek; Bryan Hansen; Jessica Scherer; Gongjun Shi; Zhaohui Liu; Andrew Green; Andrew Friskop (Plant Health Progress, 2026)
Bacterial leaf streak (BLS) caused by Xanthomonas translucens pv. undulosa is a difficult to manage disease that is seed borne. Damage from BLS can lead to significant yield loss in hard red spring wheat (HRSW) resulting in management being a high priority for growers. To increase our understanding of BLS management in HRSW, experiments were conducted to (1) Evaluate BLS seed transmission rate of HRSW varieties under greenhouse and field conditions, and (2) Assess the efficacy of seed treatments on BLS incidence and severity. Based on results from greenhouse experiments, seed transmission rate varied from 0% to 2%. Results from field experiments indicated BLS transmission for HRSW varieties ranged from 1.0% to 10.4%. Across both field and greenhouse studies, transmission rates did not consistently align with previously assigned genetic resistance scores. None of the seed treatments (Streptomyocin sulfate, sodium hypochlorite, Chenopodium quinoa saponins, and UV-C light) were able to suppress BLS incidence and severity in the field. Findings from this research has been disseminated to agricultural professionals and will influence BLS management decisions in HRSW production.